Research advances and future directions in female ADHD: the lifelong interplay of hormonal fluctuations with mood, cognition, and disease - Kooij, J. J. Sandra; de Jong, Maxime; Agnew-Blais, Jessica; Amoretti, Silvia; Bang Madsen, Kathrine; Barclay, Isabella; Bölte, Sven; Borg Skoglund, Charlotte; Broughton, Thomas; Carucci, Sara; van Dijken, Dorenda K. E.; Ernst, Julia; et al. (Frontiers in Global Women's Health, 2025)
IntroductionAttention-Deficit/Hyperactivity Disorder (ADHD) in girls and women is under-recognised and under-researched, despite increasing awareness of clinical challenges and unmet needs. This review by the Eunethydis Special Interest Group on Female ADHD, addresses current knowledge and identifies research gaps for future work. Issues in women with ADHD across the lifespan such as late diagnosis, pubertal development, sexual health, hormonal birth control, executive function difficulties, and gynaecological disorders associated with ADHD are highlighted.MethodsThe review synthesises existing literature and self-reported experiences of women with ADHD to explore the impact of hormonal fluctuations [puberty, menstrual cycle, pregnancy, (peri)menopause] on ADHD symptoms and mood disturbances. It examines the interplay of oestrogen and progesterone with dopaminergic pathways, when periods of lower oestrogen may affect cognition, as well as the manifestation of executive function deficits, and the intersection of ADHD with reproductive health.ResultsHormonal transitions exacerbate ADHD symptoms and mood disturbances, yet pharmacological research and tailored treatments are lacking. Executive function deficits manifest differently in girls and women with ADHD and are influenced by neuropsychological and neurobiological profiles. Diagnostic practices and sociocultural factors contribute to delayed diagnoses, increasing the risk of comorbidities, impaired functioning, and diminished quality of life. Undiagnosed women have increased vulnerability to premenstrual dysphoric disorder, postpartum depression, and cardiovascular disease during perimenopause.DiscussionLongitudinal, sex-specific studies incorporating hormonal status and lived experience are needed. Individualised interventions should be developed to address the unique needs of girls and women with ADHD. Addressing these gaps will advance more equitable diagnosis, management, and support for girls and women with ADHD, improving outcomes across the female lifespan.